(untitled) (Research, Society and Development, 2021)
Cervical or cervical cancer (CCU) is a female malignant tumor considered a serious public health problem and has high morbidity and mortality rates worldwide. This study aimed to evaluate the epidemiological and cytopathological profile of cervical cancers that were diagnosed in the city of Belém in the period from 2016 to 2020. An epidemiological study of a descriptive nature, with a quantitative and retrospective approach, was developed with data collection for the city of Belém, in the State of Pará, Brazil. These data were collected from the Cancer Information System (SISCAN), a database made available by the Information Technology Department of the Unified Health System (DATASUS) between the months of October and November 2021. A total of 206,614 cytopathological tests were registered during the study period, with 2019 being the year with the highest number of tests performed (32,23%). The age group with the highest number of exams was between 30 and 34 years old, corresponding to 12,87%. As for the suitability, 89,55% of the samples were classified as satisfactory. The main reason for performing the exam was for tracking (97,84%). The squamous epithelium was the most represented cytopathological sample (89,69%). Among the benign cellular alterations, inflammation had the highest number of records (82,83%) and, among the most recurrent cellular abnormalities, are low-grade intraepithelial lesions (2.98%). This study addresses the need for periodic preventive examinations, since it is a treatable disease when identified at an early stage.